Theoretical approaches to psychopathology: common cause approach vs. network approach - Ambarini, Tri Kurniati; Surjaningrum, Endang; Chusairi, Achmad (International Journal of Public Health Science (IJPHS), 2024)
The common causes (CC) approach is popular in psychopathology research, but nowadays, some experts consider this approach unfit to explain mental disorders. On the other hand, as a new approach, the network approach (NA) claims can provide a better explanation for understanding mental disorders. This study aims to determine the differences between NA and CC approach in psychopathology research. This research is a scoping review study using twelve articles. We searched for articles September-December 2020 in the Scopus and Science Direct databases. The results of the analysis of these articles show a fundamental difference between the two perspectives. The difference lies in the perspective of mental disorders, how to measure symptoms of mental disorders, treatment of mental disorders, and views on comorbidities. Each approach has advantages, although some articles support that NA is the better approach to studying mental disorders. To decide which approach is appropriate for psychopathology research, researchers should adapt it to the research objectives. Perspectives on psychopathology will determine how to answer the research questions and analyze the data.